Unsaying Law The Voice of Longing - R. Edwards (Law Text Culture, 2000)
The humble one prays for Justice. The cynic calls to him and says: "I see you pray everyday, but have you ever received a reply?". He halts his prayer and falls away, confused. In a troubled sleep a voice comes through a dream and asks "Why have you stopped praying?" – "I have never received an answer". The dream voice says: "But your longing is the response you wait for. It is the longing that draws you into union with your beloved".